Integrating the Polysocial Risk Score: Enhancing Comprehensive Healthcare Delivery - Ryan Chang; Zahir Amin; Nuh Habibullah Cheema; Samuel Yousefzai; Karam Gardezi; Aayush Shah; Zulqarnain Javed (Methodist DeBakey Cardiovascular Journal)
Social determinants of health (SDOH) are known to determine a significant portion of a person’s health, influencing downstream outcomes and widespread disparities. Screening for SDOH in clinical practice can improve efficacy of medical care, highlighting the potential for polysocial risk scores (PsRS) to help evaluate a patient’s risk of developing atherosclerotic cardiovascular disease and other conditions. This review highlights existing research about the efficacy of PsRS in practical risk assessment, current gaps in the literature, and opportunities to refine the design and implementation of PsRS in real-world clinical settings. PsRS present unique opportunities to improve traditional risk prediction models for heart disease and other conditions, particularly if they examine both individual and area-level SDOH. Future studies should assess novel methods for extracting SDOH data from patients’ medical records as well as PsRS implementation strategies that promote efficiency and patient confidentiality in real-world clinical settings.